Intussusception in 2 Children With Severe Acute Respiratory Syndrome Coronavirus-2 Infection. (8th August 2020) - Makrinioti, Heidi; MacDonald, Alexander; Lu, Xiaoxia; Wallace, Susan; Jobson, Mathew; Zhang, Furong; Shao, Jianbo; Bretherton, Jonathan; Mehmood, Tariq; Eyre, Elizabeth; Wong, Adelene; Pakkiri, Lorna; et al.
Abstract: We note that intussusception was likely associated with severe acute respiratory syndrome coronavirus-2 infection in 2 infants in Wuhan and London. The intussusception was reduced by enemas in Wuhan; the outcome was fatal. The intussusception was not reduced by enemas in London and required surgery; the outcome was favorable.